Circulating Brucella species in wild animals of the Serengeti ecosystem, Tanzania - R. M. Sambu; C. Mathew; H. E. Nonga; A. S. Lukambagire; R. B. Yapi; J. Akoko; G. Fokou; J. D. Keyyu; B. Bonfoh; R. R. Kazwala (BMC, 2021)
Abstract Background Brucellosis is a bacterial zoonosis of public health and economic importance worldwide. It affects a number of domestic animals, wild animals and humans. Human brucellosis originates from either livestock or wildlife. The species of Brucella circulating in wild animals in Tanzania is largely unknown due to insufficient surveillance. This study was carried out to identify Brucella species found in selected wildlife hosts in the Serengeti ecosystem. Methodology The study used a total of 189 archived samples that were obtained from cross-sectional studies previously conducted between 2000 and 2017 in the Serengeti ecosystem in Tanzania. Whole blood, serum and amniotic fluid collected from buffalos, lions, wildebeest, impala, zebra and hyena were available for DNA extraction. Multiplex polymerase chain reaction for B. abortus, B. melitensis, B. ovis and B. suis (AMOS PCR) and quantitative real-time PCR (qPCR) targeting the bcsp31 and IS711 genes for Brucella genus detection and the IS711 targets alkB for B. abortus and BMEI1162 for B. melitensis were used to detect Brucella strains. Results Out of the 189 samples tested, 12 (6.35 %) and 22 (11.6 %) were positive to AMOS-PCR and qPCR, respectively. Most of the positive samples were from lions (52.6 %) and buffaloes (19.6 %). Other animals that were positive included: wildebeest (13.6 %), impala (13.6 %), zebra (4.5 %) and hyena (4.5 %). Out of 22 positive samples, 16 (66.7 %) were identified as B. abortus and the other six samples did not amplify for neither B. abortus nor B. melitensis. Conclusions The detection of Brucella DNA in archived wild animal samples shows testing potential of samples collected from this population. The zoonotic species B. abortus and B. melitensis detected in wild animals have previously been reported in livestock and humans in the region. The findings suggest that, due to the contact network, some of the identified wild animal hosts in this study could be reservoirs for infections in domestic animals and humans within the Serengeti ecosystem while others are likely dead-end hosts. One Health control strategies and continuous surveillance programs in other wildlife reserved areas should be implemented to help predicting transmission in livestock and humans in the region.